Biochemical Oxygen Demand, Nitrogen, Phosphorus and Navigational Carrying Capacities of Bengoh Reservoir for Potential Aquaculture and Recreational Developments - Yee Law, Esther Lik; Ling Law, Puong (International Journal of Integrated Engineering, 2020)
This paper quantifies the biochemical oxygen demand (BOD), nitrogen (N), phosphorus (P) and navigational carrying capacities of Bengoh Reservoir for potential fish cage culture and recreational developments. The pollutant degradation coefficients (k) and pollutant carrying capacities (tons/day) of the reservoir were determined. The computed pollutant degradation coefficients were primarily based on the hydrological information of the catchment, hydraulic and operational details of the dam, and the targeted water quality standards of the river-connected Bengoh Reservoir. The maximum allowable pollutant loading rate (tons/year) defines the reservoirâ€™s maximum Waste Assimilative Capacity (WAC) on specific pollutants (BOD, N and P), while in compliance to the targeted benchmark with the receivable pollutant loadings.  It was found that the current BOD, TN and TP loading rates are 0.308 ton/day, 0.119 ton/day and 0.114 ton/day, respectively. To comply with Class I Standards of the National Water Quality Standards of Malaysia (NWQSM), the Maximum Allowable Loading Rates of BOD can be as high as 92.24 tons/day as compared to the current loading rate of 0.308 ton/day, maximum TN loading of 116.63 tons/day versus current 0.119 ton/day, and maximum TP loading  at 125.54 tons/day versus current 0.114 ton/day. It was also found that the maximum number 218 cages (225 fish/cage) of Tilapia would be allowed in Bengoh Reservoir so as to comply with Class I of NWQSM. Based on the peak level of the reservoir recreational types of use in demand and the mix of public and private access, the navigational carrying capacity of the reservoir was estimated to be about 130 boats.